Intimate Partner Violence: Barriers to Action and Opportunities for Intervention Among Health Care Providers in São Paulo, Brazil. Issue 21 (November 2021) - Evans, Dabney P.; Shojaie, Danielle Z.; Sahay, Kashika M.; DeSousa, Nancy Williams; Hall, Casey D.; Vertamatti, Maria A. F.
Health care providers (HCPs) who directly interact with women play a critical role in intimate partner violence (IPV) prevention and response. The aim of this study was to identify the structural and interpersonal barriers to IPV response among HCPs working in public health clinics in Santo André, Brazil. Eligible participants included all HCPs providing direct care to individuals at three public health clinics. Participants self-administered an adapted Knowledge, Attitudes, and Practices survey on IPV. Data were analyzed using Epi Info 7 and SAS 9.4. 114 HCPs completed surveys. Less than half of HCPs (41%, n  = 34) reported ever having asked a woman about abuse in the past year. HCPs who perceived fewer barriers were more likely to report asking about IPV. The top three reported barriers to asking women about IPV included the following: few opportunities for one-on-one interaction (77%, n  = 65), a lack of privacy (71%, n  = 60), and fear of offending women (71%, n  = 60). Fewer providers who perceived the barriers of lack of privacy asked about IPV (50.8%, n  = 33 compared with 84.2%, n  = 16; p  < .05); less providers who perceived few opportunities for private patient interactions asked about IPV (48.3%, n  = 29 compared with 75.0%, n  = 18; p  < .05). Our results support the need for a systems approach of institution-wide reforms altering the health care environment and avoiding missed opportunities in IPV screening and referring women to appropriate resources or care. Two of the most frequently reported barriers to asking IPV were structural in nature, pointing to the need for policies that protect privacy and confidentiality. Within the Brazilian context, our research highlights the role of HCPs in the design and implementation of IPV interventions that both strengthen health systems and enable providers to address IPV.